The EnvZ-OmpR Two-Component Signaling System Is Inactivated in a Mutant Devoid of Osmoregulated Periplasmic Glucans in Dickeya dadantii - Caby, Marine; Bontemps-Gallo, Sébastien; Gruau, Peggy; Delrue, Brigitte; Madec, Edwige; Lacroix, Jean-Marie (Frontiers in Microbiology, 2018)
Osmoregulated periplasmic glucans (OPGs) are general constituents of alpha-, beta-, and gamma-Proteobacteria. This polymer of glucose is required for full virulence of many pathogens including Dickeya dadantii (D. dadantii). The phytopathogenic enterobacterium D. dadantii causes soft-rot disease in a wide range of plants. An OPG-defective mutant is impaired in environment sensing. We previously demonstrated that (i) fluctuation of OPG concentration controlled the activation level of the RcsCDB system, and (ii) RcsCDB along with EnvZ/OmpR controlled the mechanism of OPG succinylation. These previous data lead us to explore whether OPGs are required for other two-component systems. In this study, we demonstrate that inactivation of the EnvZ/OmpR system in an OPG-defective mutant restores full synthesis of pectinase but only partial virulence. Unlike for the RcsCDB system, the EnvZ-OmpR system is not controlled by OPG concentration but requires OPGs for proper activation.